Pengendalian Jamur Akar Putih (Rigidoporus sp.) Penyebab Penyakit Layu pada Tanaman Cengkeh ( Syzygium aromaticum L. ) secara Hayati dan Nabati di Rumah Kaca - I KOMANG JULIARTA; MADE SUDANA; WAYAN ADIARTAYASA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT Controlling Root Fungus White (Rigidoporus sp.) Causes wilt disease in plants Clove (Syzygium aromaticum L.) in Biological Greenhouse Control of Root White Fungus (Rigidoporus sp.) Causes wilt disease on clove plants (Syzygium aromaticum L.) by using Biological and Botanical controls in Greenhouse, Aims of this study to determine the effectiveness of plant-based materials and the biological control of wilt disease on cloves plants. The method used in this study was a completely randomized design. This research was conducted in the greenhouse using 10 treatments and 3 replications. The results showed that the treatment of some biological and Botanical controls in the trials showed that the treatment of P. fluorecens have the ability to encourage vegetative growth of cloves plants, and Trichoderma sp. is able to reduce the degree of damage to the plants wilt disease of cloves. Keywords: Cengkeh, the degree of damage, Rigidoporus sp., biological and botanical controls